Rumahku Madrasahku, a Parenting Education for Young Bajo Mothers of Soropia - Mayasari, Ros; Rahmawati, Rahmawati; Hasniran, Hasniran; Alifuddin, Muhammad; Walhidayat, Andi Arif; Sabil, Nanda Ayu Puspita (UI Scholars Hub, 2023)
This paper discusses an educational activity program for the indigenous people of Bajo in Southeast Sulawesi, Indonesia, aiming to improve parenting knowledge among young mothers. It addresses issues related to their identity as indigenous people, their self-esteem, and their way of upbringing of children. The issue of low self-esteem among the Bajo community often leads to adverse effects on their learning motivation, future orientation, and exclusivity, particularly in children. This situation becomes more complicated due to the societal tendency toward child marriage, especially among the Bajo people in Leppe Village. Rumahku Madrasahku (meaning My Home is My School) is a program proposed using an adult learning approach to introduce egalitarian parenting and teach children about self-worth. Departing from Brofensbrenner’s ecological theory, this program highlights the role of the family as a basis for encouraging a positive sense of self-worth in the Bajo children. A series of activities are planned and prepared using Participatory Action Research (PAR), from sharing sessions, lectures, question and answer, reflection, and assignment exercises. The program utilizes the mothers’ knowledge and experience in parenting to be further developed parenting strategies. It provides young mothers with a greater understanding of the self esteem concept, the significance of children’s self esteem, and parenting strategies that can increase children’s self-esteem and enhance their awareness of their roles and responsibilities as mothers and parents. This educational program has only initiated the first phase of providing the young mother with understanding, awareness, and skills that might be required for egalitarian parenting. Even though it is challenging and may take some time, changes in knowledge and attitudes towards parenting can be observed as a result of the program, thus calling for continuous and further systematic assistance in the future.